THE DIFFERENCES OF BEHAVIOUR TOWARDS PREGNANCY READINESS AMONG PREGNANT WOMEN BASED ON PARITY - Fitri Indah Pratiwi; Wahyul Anis; Aditiawarman Aditiawarman; Reny I’tishom (UNIVERSITAS AIRLANGGA, 2020)
Abstract Background : Low pregnancy planning can cause unwanted pregnancy, abortion, loss of reproductive health, domestic violence until death. 40% of 85 million pregnancies in the world are unplanned and 38% end with abortions, miscarriage and unplanned childbirth. Unplanned pregnancy are associated with an increased risk of birth outcomes, including preterm birth, low birth weight (LBW), high risk of congenital anomalies, and developmental delay. Most woman who have plan to get pregnant don’t prepare their pregnancy as well. Women who have children (Multiparous) having unreadiness of pregnancy as same as women who do not have children (Nulliparous). Therefore, pregnancy planning is required to avoid risks so that women become more prepared on facing the pregnancy. This study aimed to analyze the differences behaviour toward readiness of pregnancy among pregnancy women based on parity. Method : This study used observational analytical research with cross sectional approach. The sampling technique used was total sampling which was conducted for 2 months and the sample obtained 92 pregnant women (include nulliparous, primiparous and multiparous) who met the inclusion criteria. The collected data was analyzed by Fisher Exact levels with a degree of α = 0.05. Result : The study showed there were 12 respondents who ready to face pregnancy. Meanwhile, there were 80 respondents who were not ready enough to face pregnancy, it was based on the result of Fisher Exact test with the value obtained was P value = 0.223 (P > 0.223). Conclusion : This showed that there was no difference of attitudes about pregnancy readiness of nulliparous, primiparous and multiparous woman